Preparo e caracterização de membranas de quitosana modificadas com poli (ácido acrílico) - Lima, Maria do Socorro Pereira de (2006)
The aim of this study was to generate an asymmetric biocompactible and biodegradable chitosan membrane modiﬁed by the contact with a poly(acrylic acid) solution at one of its sides at room temperature and 60◦C. The pure chitosan membrane, as well as the ones treated with poly(acrylic acid) were characterized by infrared spectroscopy (FTIRATR) at angles of 39◦, 45◦ and 60◦ , swelling capacity in water, thermal analysis (TG/DTG), scanning electronic microscopy (SEM) and permeation experiments using metronidazole at 0,1% and 0,2% as a model drug. The results conﬁrmed the presence of ionic interaction between chitosan and poly(acrylic acid) by means of a polyelectrolyte complex (PEC) formation. They also showed that such interactions were more effective at 60◦C since this temperature is above the chitosan glass transition temperature wich makes the diffusion of poly(acrylic acid) easier, and that the two treated membranes were asymmetrics, more thermically stable and less permeable in relation to metronidazole than the pure chitosan membrane